A prospective study of colonic tumors and accuracy of CT pneumocolon in staging colonic carcinoma - Anand Shrikant Gajakos; Vikas R Lonikar; Jyoti K Tapadia (Asian Journal of Medical Sciences, 2023)
Background: Preoperatively, reliable diagnosis of the amount of dissemination of a colorectal cancer not only reveals the probable outcome but also aids care. There have been few studies on the use of spiral computed tomography (CT) pneumocolon for pre-operative staging of colorectal cancer. Aims and Objectives: Therefore, the present study was undertaken to evaluate colonic masses and determine the accuracy of spiral CT pneumocolon in staging colonic carcinomas. Materials and Methods: This prospective and hospital-based study was conducted for 2 years of period at the Department of Radiodiagnosis and comprised 75 patients who were sent for CT abdomen. All patients of all ages referred for CT examination with symptoms and/or clinical suspicion of colonic cancer, suspected colonic tumor, blockage, or stricture on barium studies or colonoscopies, or worrisome sonographic abnormalities, including colonic wall thickening and other features indicative of colon cancer were included in the study. Results: The predominated gender is male (63%) than female (37%). The observations reveal that, in malignant diseases, bleeding per rectum was the most prevalent symptom, while discomfort in the abdomen was the most common symptom in benign pathologies. CT pneumocolon correctly diagnosed cancer in all 57 patients, although three benign lesions were incorrectly categorized as malignant. The sensitivity and specificity for differentiating benign from malignant lesions were both 100% (57/57) and 83.3% (15/18). Conclusion: CT pneumocolon looks to be a non-invasive and quick inquiry that clearly displays the lumen of the colon, wall of the colon, surrounding structures, extraluminal component of colonic lesions, and metastases and gives useful information preoperatively.